Frozen storybook collection eaudiobook - Disney Press (Frozen., 2017)
Frozen fun! Join all your favorite Frozen characters on one thrilling journey after another! Visit the snowgies with Olaf, participate in an ice-carving contest with Anna and Kristoff, celebrate Elsa's birthday, and more! This enchanting collection brings the magic of Arendelle to life! This expanded audio edition contains the Frozen Storybook Collection , featuring eighteen stories, plus an additional nine stories not included in the print version.